Designing of Microwave Metamaterial Biosensor for Water Pollution Monitoring - Wee Kai Boon; Zainal Abidin, Zuhairiah; Adel Yahya Isa Ashyap (Journal of Electronic Voltage and Application, 2021)
This paper focuses on developing a microwave metamaterial-based Microstrip Ring Resonator for water quality monitoring. Water pollution is increasing at an alarming rate, worsening pollution and destroying natural habitats. This paper aims to design a metamaterial-based resonator, analyse its performance with various biosamples, and then fabricate the designed product to validate the sensing performance. For this purpose, Computer Simulation Technology (CST) is used to design and simulate the proposed biosensor, with Rogers-RO3003 as the substrate material. In addition, for the Proof of Concept (POC), different types of liquid materials under test were used in simulation and measurement. The procedures begin with the design and simulation of the MRR using CST, followed by the fabrication stage when the simulation produced the desired results, and finally, laboratory measurements for data collection. The sensing area of the microstrip ring resonator was observed through electric field distribution, where a gap was introduced in the ring structure. The results show that the proposed structure of the resonator is able to distinguish different types of liquids that are placed in the sensing gap, by shifting the resonance frequency based on their dielectric constant. In summary, a new metamaterial-based microstrip ring resonator is produced to monitor liquid quality. The concept behind the paper was proven through simulations and experiments where it is suitable to be used as a sensing algorithm. In future work, this product could be used to monitor residue in our clean water, such as rivers, to minimise the polluted drinking water risk.